Maintenance of air handling unit at Ministry of Finance, Putrajaya / Muhammad Hasif Hazman Khalid - Khalid, Muhammad Hasif Hazman (Universiti Teknologi Mara, Perak, 2016)
Practical training is an important syllabus that needs to be completed by the student before they finish their study. This practical training is aimed to expose the student to the real world of work. All the knowledge that had been taught by lecturer in the class can be implemented by students during their practical training. For my practical training, the field of work that I choose is maintenance field. This field of work is more focus to the post-construction work. Maintenance is really important, this is because after the building was finished, its need to be well maintained to prolong its life span. I made my practical training at the Complex of Ministry of Finance, Persiaran Perdana, Presint 2, 62592, Putrajaya, Malaysia. I had begun my practical training started from 1st June 2016 and ended on 30 September 2016. In this practical training report, I will explain on how maintenance work of the air handling unit had been conducted in my case study.